Managing hydrocephalus in patients with leptomeningeal disease: a multicenter retrospective analysis - Alhalabi, Obada; Klein, Lukas; Wasilewski, David; Mellal, Amine; Büsken, Carmen; Buszello, Clara; Cossu, Giulia; Eyüpoglu, Ilker Y.; Unterberg, Andreas; Vajkoczy, Peter; Schackert, Gabriele; Messerer, Mahmoud; et al. (International journal of cancer, 2025)
Leptomeningeal disease (LMD) represents a terminal condition of tumor cell seeding that can cause symptomatic hydrocephalus. With improved survival rates under systemic therapy, the role of cerebrospinal fluid (CSF) drainage through ventriculo-peritoneal shunt (VPS) or Rickham reservoir (RR) placement in LMD patients is gaining more relevance. This study aimed to compare outcomes of both modalities in a multicentric contemporary cohort. A retrospective analysis of medical charts in patients receiving VPS for LMD and malresorptive hydrocephalus in two neurosurgical centers between 2006 and 2021 yielded 64 patients. The most common underlying oncological conditions were breast (n = 32, 49%) and non-small cell lung cancer (NSCLC, n = 16, 25%). The median time between primary and LMD diagnosis was 23.3 months (11.2 to 43.4 months). Symptoms of intracranial hypertension were relieved in 79% of cases (n = 50) after shunting, with 42 (66%) and 32 patients (50%) receiving systemic and intrathecal therapy, respectively. A further multicenter analysis comparing patients receiving VPS with patients receiving RR (with regular tapping) included 155 patients (VPS: n = 80, 52%; RR: n = 75, 48%). Compared to VPS, RRs were associated with a lower surgical revision rate (8% vs. 24%, p = 0.009). There was no difference in median overall survival in VPS patients (118 days) compared to RR patients (80 days, p = 0.180). Given this data showing a short and comparable survival of patients under both modalities with a lower RR complication rate, a rationale for an initial Rickham implantation in LMD patients with hydrocephalus, with later VPS conversion for long-term surviving patients, could be contemplated.